Regressed Papillary Thyroid Carcinoma with Anaplastic Transformation into Lymph Node Metastasis: Case Report with Review of the Literature - Bozidar Kovacevic; Bojana Rancic; Sasa Jovic; Snezana Cerovic; Vesna Skuletic; Jelena Karajovic; Milka Gardasevic; Gordana Supic; Kennichi Kakudo (Diagnostics)
Background: Small papillary thyroid carcinomas with the largest dimension of 10 mm are slow-growing and self-limiting tumors, most of which have no potential for progression, rarely becoming clinically evident carcinomas or undergoing regressive changes. Their anaplastic transformation, primarily in the thyroid gland or into lymph node metastasis, is extremely rare. Case Presentation: A 66-year-old female patient was admitted to our hospital for diagnostics and treatment of a large tumor on the left neck side. Preoperative imaging and cytological findings of the neck tumor suggested metastasis of papillary thyroid carcinoma. Total thyroidectomy and metastasectomy were performed. In the final diagnosis, anaplastic transformation of the papillary thyroid carcinoma’s metastasis in the neck was confirmed. Opposite to advanced dedifferentiation of metastasis, primary tumor foci in the thyroid were regressed and replaced with sclerosis and microcalcification. The synchronous co-occurrence of incidental primary thyroid carcinoma and anaplastic thyroid carcinoma originating from ectopic cervical thyroid tissue was considered diagnostically. Conclusions: The case highlights the necessity of regular monitoring of the thyroid and neck lymph nodes for patients under active surveillance, including those with small calcified tumor foci. This paper also comprehensively reviews the existing literature on this topic.